Potential ASEAN-Japan Collaboration for Regional Missile Test Confidence-and Security-Building Measures - Haykal, Maula Mohamad (Universitas Airlangga, 2025)
This paper explores the possibility of a regional Confidence-and Security Building Measure (CSBM) focused on long-range missile tests. Currently, the Indo-Pacific region is marked by the proliferation of long-range surface (land and sea) strike missiles by both major powers and smaller states, including member countries of the Association of Southeast Asian Nations (ASEAN). The paper seeks to determine whether a CSBM initiative—originally a concept developed in Europe—between ASEAN and other countries in the region is feasible. Using Japan—a trusted ASEAN partner—as a case study, this paper applies the criteria proposed by David Capie and Paul Evans for creating a successful CSBM in the Asia-Pacific region to examine whether an ASEAN-Japan collaboration on missile test CSBMs would be viable. The paper begins by describing the current regional dynamics, followed by a brief overview of the CSBM concept. The subsequent section presents three arguments supporting the viability of ASEAN Japan collaboration on CSBMs, while also discussing potential obstacles that could hinder this partnership and the broader socialization of missile test CSBMs across the region. Keywords: CSBM, long-range surface strike missiles, Indo-Pacific, ASEAN, Japan.